(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This study is devoted to evaluating fuel efficiency in fuel-injected gasoline engines using a hydrogen–gasoline mixture. The research analyzes the theoretical foundations of the combustion process, the physical and chemical properties of hydrogen, and the influence of hydrogen enrichment on engine performance and fuel consumption. Experimental investigations were conducted under various engine operating modes to assess fuel economy, exhaust emissions, and combustion stability. The results show that the addition of hydrogen improves combustion efficiency, reduces ignition delay, and ensures more complete fuel combustion. As a result, gasoline consumption decreased by approximately 8–15%, particularly under urban driving and medium-load conditions. In addition, the concentrations of carbon monoxide (CO) and unburned hydrocarbons (HC) in exhaust gases were significantly reduced, indicating improved environmental performance. The findings demonstrate that hydrogen enrichment can enhance engine efficiency and reduce environmental impact without requiring major modifications to existing fuel-injected engines.